The effect of Qur’anic recitation on health: a brief review on previous clinical studies - Taib, Mai Nurul Ashikin; Sharifudin, Mohd Ariff; Che Ahmad, Aminudin (Faculty of Medicine, International Islamic University Malaysia, 2013)
Among the benefits of listening to or reciting the Qur’an is its healing effects as. In the past, this has only been shown through observational or personal experiences. The main objective of this review is to analyze available clinical studies performed related to the effects of Qur’anic recitation on human beings. Hence, this offers a research agenda to guide future studies to explore this field. The findings on related clinical studies were obtained from electronic and manual searches. Keywords used included: Qur’anic healing, Qur’anic recitation, psychological and physiological outcomes. Studies which met the selection criteria were retrieved and reviewed. These included articles or papers published in English or Malay/ Indonesian in language since the year 2000 with at least one psychological or physiological outcome measure. A total of five clinical studies were reviewed. The themes of these studies were mainly the effect on psychology, physiology or haemodynamics of human subjects. Only one was experimental in nature while the other four were observational. Four of the studies used Surah Yassin (Chapter 36). The whole Qur’an was used in the fifth study. Three of the studies involved normal human subjects while the other two involved critical care patients or adult working women, respectively. Positive significant results were reported in studies related to psychological effects. However, studies related to physiological outcomes were not significant. Limitations of the studies included the study design, sample selection, small sample size, inconsistency in the measures used, and invasiveness of monitoring. Although some of the studies showed positive psychological results, a more comprehensive study design should be done for a more conclusive outcome. These studies were not performed to substitute our faith as Muslims on the healing effects of the Al-Qur’an. The scientific evidences will strengthen our faith and the practice on patients can be integrated into the current mainstream medicine. Better researches can be performed and further explored.